2022
DOI: 10.53730/ijhs.v6ns5.9070
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnetic field on productive and hysiological performance in broiler breeder

Abstract: The experiment was conducted to determine the effect of magnetic field on the productive and physiological performance of Ross 308. The experimental flock consist of 60 hens and 10 cocks of broiler breeders, which randomly divided into four groups and distributed on the treatments with three replicates for each treatment. The treatments included the control treatment (T1), exposure the stored semen to 803 gauss magnetic field for 24 hours (T2), exposure the fertile eggs to 250 gauss magnetic field for 72 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…In a study by Yu et al, [35] exposing broiler breeder to 250 gauss MF for 8 weeks resulted in a significant increase in their plasma glucose levels compared to the control group. The reduction in carcass percentage in all treated birds is in agreement with [36] who reported a significant decrease in body weight gain of meattype breeder eggs exposed to 18 Gauss MF at 50 Hz for 75 min. In contrast, Shafey et al [37] showed significant increase in the weight of rats exposed to MFs of 5 and 8mT for 3 weeks.…”
Section: Carcass and Internal Organssupporting
confidence: 91%
“…In a study by Yu et al, [35] exposing broiler breeder to 250 gauss MF for 8 weeks resulted in a significant increase in their plasma glucose levels compared to the control group. The reduction in carcass percentage in all treated birds is in agreement with [36] who reported a significant decrease in body weight gain of meattype breeder eggs exposed to 18 Gauss MF at 50 Hz for 75 min. In contrast, Shafey et al [37] showed significant increase in the weight of rats exposed to MFs of 5 and 8mT for 3 weeks.…”
Section: Carcass and Internal Organssupporting
confidence: 91%
“…In contrast, other studies used different levels of vitamin E supplementation (0, 150, 250 and 350 mg/kg of diet) and reported no significant differences in feed consumption and feed conversion efficiency in their progeny generation 14,15 indicated an improvement in weight gain when selenium was added (0.4 mg/kg) to the diet of broiler at 1-6 weeks of age, (16) indicated no significant differences in weight gain when adding sodium selenite to broiler diets at a 1 mg/kg rate at 15-27 days of age. There are many global hybrids used widely in Iraq to produce broilers for local consumption, and sometimes the broiler industry imports chicks or eggs for hatchery, besides there are many enterprises that reared broiler breeders to produce hatching eggs, and there are many studies aimed to improve their performance in the Iraqi environment [17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%